Delayed Recognition of an Ureteropelvic Junction Obstruction in a Young Adult Female - Ariel Schulman; Jean Paul Wuilleumier; Ervin Teper (Case Reports in Urology)
A percentage of ureteropelvic junction obstruction cases are clinically silent in childhood and manifest symptoms in adults. Herein we present a 25-year-old female with several years of intermittent flank pain and abdominal symptoms with prior inconclusive diagnostic workup including abdominal imaging without hydronephrosis. Ultimately, a CT scan performed during an acute pain crisis clearly identified right-sided hydronephrosis. The keys to diagnosis are awareness of this entity, a detailed history, and obtaining imaging studies during a crisis. The patient subsequently underwent a right robotic-assisted laparoscopic pyeloplasty with preservation of a lower pole crossing vessel. We highlight noteworthy features of the clinical presentation and surgical repair.